Highly efficient synthesis of chiral aromatic ketones via Rh-catalyzed asymmetric hydrogenation of β, β-disubstituted enones. Issue 66 (3rd August 2017) - Zhang, Tao; Jiang, Jun; Yao, Lin; Geng, Huiling; Zhang, Xumu
Abstract : A series of chiral aromatic ketones were achieved with excellent enantioselectivities via Rh–ZhaoPhos catalyzed asymmetric hydrogenation of β, β-disubstituted enones. Abstract : A succinct and efficient protocol was developed for the synthesis of chiral aromatic ketones via asymmetric hydrogenation of β, β-disubstituted enones with rhodium catalysts based on chiral bisphosphine thiourea ligands. A series of substrates (17 examples) was smoothly catalyzed to afford the corresponding chiral aromatic ketones in high conversions (>99%) with excellent enantioselectivities (up to 96% ee).